Pengelolaan “Bank Sampah” Berbasis Masyarakat sebagai Alternatif Meningkatkan Ekonomi Warga RT 004/RW 09, Cikarang Utara–Bekasi - Purwanto Purwanto (ACADEMICS IN ACTION Journal of Community Empowerment, 2019)
Bekasi government has a sense of a desire to reduce the volume of waste going into landfill by implementing the concept of reduce, reuse, recycle (3R). The government's program to reduce waste volume has fostered new innovations from the community by establishing a ‘Bank Sampah’. Bank sampah is the concept of dry waste collection and sorting as well as having appropriate management of banking, not the money saved, but trash. Empowerment of citizens can be done by counseling, education, training with the method of interaction and communication, as well as dialogue. The objective of this activity is to describe and analyze the factors that drive, the impact and the constraints of the formation and functioning of bank sampah at RT 004/RW009, Cikarang Utara, Bekasi. The method was observation, interview, and documentation. The results showed that there are some factors that encourage it, namely the factors of government, society and the private sector (entrepreneurs). Support comes from the community such as of PKK driving team, environmental cadres, citizens, stall traders both factories, collectors of used goods and individual scrubbers. Bank sampah provides benefits to citizens, especially the direct benefits with reduced waste generation in the community, the environment becomes more clean and beautiful, green, comfortable, and healthy as well as the economic independence of citizens. Integrated waste management can stimulate creativity and innovation so as to improve the social welfare.